(3GdfXGe GdbGfhfj ddJhbjY GdGdcJQhfj aj VhA GdGJaGbjGJ GdOhdjI h GdJTQjYGJ GdYQHjI h GdbGfhf (B15 (3dSfI(B2004 /s - (3agej, NGdO eUWais ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2007)
(3jVe eGgjI hCgejI GdJhbjY aj eLGd GdGKHGJ, JYQja GdJhbjY , CTcGd GdJhbjY , hXGFa GdJhbjY hTQhWg heGgjI GdJhbjY GdGdcJQhfj hJejjRg HGdEVGaI Edi JYQja GdJhbjY GdGdcJQhfj heOi JYdbg HGdfXGe GdYGe , SeGJ heejRJ GdJhbjY GdGdcJQhfj , UhQ GdJhbjY GdGdcJQhfj, MLjI GdeMQQGJ GdGdcJQhfjI aj GdGKHGJ, MLjI GdeMQQ GdGdcJQhfj aj GdGKHGJ , MLjI GdJhbjY GdGdcJQhfj aj GdGKHGJ, hGdaUd GdKGdK jVe GdGWGQ GdJTQjYj hGdJbfj ddJUOjQ Ydi GdJhbjY GdGdcJQhfj, GdJfXje GdbGehfj gjFI GdJfejI UfGYI JcfhdhLjG GdeYdheGJ , LgGJ GdJUOjb GdGdcJQhfj , TgGOGJ GdJUOjb GdGdcJQhfj GdeSDhdjI GdeOGfjI GdfGTFI Yf GdJhbjY GdGdcJQhfj, GdeSDhdjI GdYbOjI aj eLGd GdJhbjY GdGdcJQhfj , GdeSDhdjI GdJbUjQjI aj eLGd GdJhbjY GdGdcJQhfj , CKQ JhGaQ CQcGf GdeSDhdjI (B( (3GdJYhjV (B)(3, GdeSDhdjI GdeOfjI ddTNU GdeYfhj, JWHjbGJ GdJhbjY GdGdcJQhfj(B. s
(3HjHdjhZQGajG(B: (3U(B. 302s
Keywords: (3GdEJaGbjGJ GdOhdjIs; (3GdMbhb GdeOfjIs; (3JcfhdhLjG GdeYdheGJs; (3bhGfjf h JTQjYGJs